PELAKSANAAN PEMBELAJARAN BERBASIS ONLINE (MEDIA GOOGLE CLASSROOM) DALAM TANGGAP WORK FROM HOME MASA PANDEMI VIRUS COVID-19 DI FAKULTAS EKONOMI DAN ILMU SOSIAL UNIVERSITAS ISLAM NEGERI SULTAN SYARIF KASIM RIAU - pivit septiary chandra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The application of learning with the online system is a consequence of the spread of the Covid-19 Virus in the world of education. Google Classroom is a medium to help educators / teachers in the learning process. This has also been applied in the Faculty of Economics and Social Sciences. There are potential obstacles in the online learning process using google classroom in Uin Suska riau environment, therefore researchers are interested in researching the application of the learning system using Google classroom. This study used a descriptive qualitative method with survey techniques. The study was conducted on October 5, 2020, December 15, 2020, with the number of respondents as many as 390 students in the Faculty of Economics and Social Sciences, UIN Suska Riau. Data obtained through questions distributed to all respondents in the form of google form then the data is analyzed with a description description. The result of the research is that Google Classromm media really helps educators and teachers to continue to carry out the learning process in the midst of the Covid-19 virus epidemic, but there needs to be attention to the quality of learning when learning is carried out in a long distance Most of Fekonsos students of UIN SUSKA Riau still do not feel that they understand the knowledge conveyed by learning using Google Classroom.Keyword: online learning, google classroom, covid-19 virus